Impact of Covid-19 on Tourism Business in Pokhara Nepal - Khatiwada, Shreekanta S.; Sharma, Ramji; Ranabhat, Suresh (Janapriya Journal of Interdisciplinary Studies, 2021)
None of the sectors in human society is out of the assault of covid-19 pandemic. Every sphere of human life is affected by this contagion virus nonetheless the severity of influence and impact may vary Tourism is one of the highly injured sectors during on-covid period and so as the situation of Pokhara and its vicinity. This paper, therefore, is an attempt from ‘situation analysis perspective’ to have a bird’s eye view of the impact and implication of covid pandemic over the tourism industry of Gandaki province with special focus on Pokhara by taking three vital variables; investment, employment and volume of transactions. It’s a kind of ‘situation analysis research’ based mainly on secondary information backed up by sufficient primary data and information. The two main impacts of Covid-19 over the tourism domain of Pokhara and its vicinity seem to be the shutdown of substantial numbers of hospitality businesses and the bulk loss of employment from tourism sector.